AN INTERPRETING ANALYSIS OF IU’S HIT SONGS THAT ACHIEVE PERFECT ALL-KILL - Gita Tiara Putri Quraisyma Pramudita (PROJECT (Professional Journal of English Education), 2021)
Nowadays, all about K-Pop (Korean Pop) widely known in the world, South Korea’s music industry is known to have a music chart system that is very influential on the career and achievement of a singer. The system is to measure the success of a group or solo singer when they release a song. Some of the terms that are known by most K-Pop fans are real-time all-kill (RAK) certificates, certified all-kill (CAK), and perfect all-kill (PAK). Songs that receive RAK, CAK, or PAK certificates, can be interpreted as best-selling songs played on digital music services in Korea. This is an interpreting analysis of IU’s hit songs taken from 2011 until 2020, aimed to see what linguistic factors that makes them hit and achieve PAK. This research used a qualitative method. This research concluded 8 from 15 of IU songs make it achieve PAK because of numerous factors such as: the music, the instrument, the singing style, and the lyric with figurative languages. In academic environments, teacher may teach the students how to analyze song lyric because it is useful to teach vocabulary, idiom, and also elements of poetry. Keywords:  Analysis, Interpreting, Music, IU